Antennal and maxillary palp morphology, and sensillar equipment, of the spruce bark beetle predators, Medetera signaticornis and Medetera infumata (Diptera: Dolichopodidae). (January 2023) - Sousa, Maria; Ignell, Rickard; Pollet, Marc; Green, Kristina K.; Becher, Paul G.; Birgersson, Göran
Abstract: Many long-legged Medetera flies are natural enemies of bark beetle pests, which they detect using olfactory cues, likely through olfactory sensilla on the antennae and maxillary palps. Morphological characterisation of olfactory sensilla among insects can provide a basis for future taxonomic, phylogenetic or electrophysiological studies. Scanning electron microscopy was used to describe the morphology of olfactory organs and sensillar equipment of Medetera signaticornis and M. infumata . Three different olfactory sensillum types were found in both fly species, sensilla trichodea, s. basiconica and grooved pegs. Based on size and wall structure, s. trichodea and s. basiconica were categorised into different subtypes. Sharp-tipped curved s. trichodea, and small, large and thin s. basiconica were found on the antennal postpedicel of M. signaticornis adults, while grooved s. basiconica were found in M. infumata. The density of sharp-tipped long s. trichodea was significantly higher in males compared to females, and in M. signaticornis compared to M. infumata . Long-grooved s. basiconica were found grouped in a small pit on the maxillary palps of both species. Comparison of our results with the limited available ecological data suggests that differences in numbers of specific sensillum types may reflect adaptations related to olfactory-driven behaviours such as host seeking. Highlights: Medetera flies are important natural enemies of bark beetles, such as Ips typographus . The flies are known to use olfactory cues to detect their prey. By SEM, we analysed the peripheral olfactory systems of two Medetera species. M. signaticornis and M. infumata showed similar palpal morphology. However, the species differed in relation to the antennal sensillar equipment.